Pengembangan Keterampilan dan Pengetahuan Sumber Daya Manusia Kelompok PKK dalam Mendukung Industri Kreatif di Daerah Pedesaan - Radzaky, Deby Putri; Giriati, Giriati; Rinita , Ayu; Qori'ah, Cinta; Sahrani, Alisa Putri; Maharani, Deswinda Triska (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Teluk Kapuas Village is one of the villages in Sungai Raya Sub-district, Kubu Raya Regency. The problem faced by the PKK Group of Teluk Kapuas Village is that it does not have a typical product that can be developed into a superior product. To overcome this problem, KKM-PKM students strive to provide solutions through entrepreneurship training in the form of herbal drink making training and socialization of the importance of good product packaging and Handicraft Making Training from Feather Wire (Pipe Cleaner). The implementation of Herbal Drink Making Training and Handicraft Making Training from Feather Wire (Pipe Cleaner) in the PKK group of Teluk Kapuas Village begins with an observation or survey stage to find out the social conditions and problems faced by the PKK group. Next, coordination and licensing were carried out with the head of the PKK group of Teluk Kapuas Village to carry out training activities. After coordination and licensing, it was agreed that the training would be held twice a month, on July 12 and July 20, 2024. These training activities can have a positive impact and motivate the PKK members of Teluk Kapuas Village to be more creative and innovative. These training activities can have a positive impact and motivation for PKK members of Teluk Kapuas Village to be more creative and innovative. By holding this training, it can also train more qualified Human Resources (HR), and motivate participants in starting a business. In addition, from the series of activities that have been carried out, it is hoped that they can help stimulate the entrepreneurial spirit of all PKK members and provide new ideas that can be used as typical products of the PKK group in Teluk Kapuas Village, so as to improve better Human Resources (HR).